EXERCISING THE RIGHT TO PROTECTION OF HUMAN AND CIVIL RIGHTS AND FREEDOMS IN THE EUROPEAN COURT OF HUMAN RIGHTS - Zhukova , Natalya; Arzumanova , Silva; Novikov , Andrey; Dyachenko , Olga; Suhanov , Aleksandr (Revista Inclusiones, 2019)
This paper is based on the analysis of some international legal acts, monographic and scientific publications. It also considers practice of hearing cases on protection of human and civil rights and freedoms by the European Court of Human Rights and implementation of its rulings in European countries. This analysis made it possible to identify some of the problems associated with evaluating the effectiveness of the work of this court. The conclusions are formulated about the attempts to create a world-wide common practice of judicial resolution of disputes related to the violation of the right to protection of human and civil rights and freedoms.